2009
DOI: 10.1016/j.bmc.2008.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-guided isolation of cytotoxic constituents of Brucea javanica collected in Vietnam

Abstract: Five new triterpenoids (1-5), together with two known quassinoids, bruceantin (6) and bruceine A (7), and a known flavonolignan, (−)-hydnocarpin (8), were isolated from the chloroform-soluble subfraction of a methanol extract of the combined twigs, leaves, and inflorescence of Brucea javanica collected in Vietnam. The structures of the new compounds 1-5 were established on the basis of spectroscopic methods. All isolates were evaluated for cytotoxicity against a small panel of human cancer cell lines. Quassino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Recently, much attention has been paid to the Brucea genus and its chemical constituents because of its manysided activities. Many chemical constituents have been isolated from Brucea genus, including quassinoids, alkaloids, triterpenoids, and flavonoids [2][3][4][5]. Its core components are quassinoids, which possess various biological activities including anti-tumor [4], anti-malarial and anti-babesial [6,7], anti-viral [8], anti-bacterial [9,10] and hyperglycemic [11] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the Brucea genus and its chemical constituents because of its manysided activities. Many chemical constituents have been isolated from Brucea genus, including quassinoids, alkaloids, triterpenoids, and flavonoids [2][3][4][5]. Its core components are quassinoids, which possess various biological activities including anti-tumor [4], anti-malarial and anti-babesial [6,7], anti-viral [8], anti-bacterial [9,10] and hyperglycemic [11] activities.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Many studies have shown that BJO has a variety of pharmacological activities, including anti-HIV (human immunodeficiency virus), antimalarial, antituberculosis, cytotoxic, and antitumor activities. 6 BJO exerts antitumor effect in many ways: 7 1) affect tumor cell cycle and kill tumor cells of G 0 , G 1 , S, G 2 , and M phases by inhibiting the synthesis of DNA, RNA, and protein; 8 2) destruct biological structure of tumor cells; 9 3) activate Caspase-3 10 and inhibit the expression of NF-κB, 11 mutant P53, and B-cell lymphoma-2 (Bcl-2); 12 and 4) reverse multidrug resistance in cancer cells and inhibit the activity of topoisomerase-II. 13,14 In addition, BJO can protect normal bone marrow and increase the number of white blood cells, promoting the body's immune system.…”
Section: Liu Et Almentioning
confidence: 99%
“…It was also found that compound 36 inhibited the expression of cyclins A, B, and E, in addition to reducing the levels of phospholyrated AKT and PRAS40 (Spear et al 2013). The known quassinoids bruceantin ( 17 ) and bruceine A ( 18 ) were highly active against the human cancer cell lines Lu1 (lung), LNCaP (hormone-dependent prostate), and MCF-7 (breast), with IC 50 values in the nanomolar range, whereas rotenoids 44–45 exhibited significant growth inhibition against 697 human acute lymphoblastic leukemia cells with IC 50 values of less than 1 μM (Bueno Pérez et al 2013; Pan et al 2009). …”
Section: Compounds Isolatedmentioning
confidence: 99%
“…The cytotoxicities of bruceantin ( 17 ) and bruceine A ( 18 ) against MCF-7 cells were enhanced about 10-fold when combined with the flavonolignan (−)-hydnocarpin ( 19 ), isolated from Brucea javanica (Pan et al 2009). In a similar way, (−)-hydnocarpin ( 19 ) at 10 μM also produced a significant potentiating effect in vincristine cytotoxicity at concentrations of 1.5 and 0.75 nM against 697 cells resulting in 83% ( p = 0.03) and 61% ( p < 0.0001) increase in growth inhibition, respectively, when compared to vincristine treatment alone.…”
Section: Compounds Isolatedmentioning
confidence: 99%